Renal allograft survival in transplant recipients with focal segmental glomerulosclerosis - Takahiro Shinzato; Yoshitaka kinoshita; Taro Kubo; Toshihiro Shimizu; Koji Nanmoku; Takashi Yagisawa (Society of Diabetic Nephropathy Prevention, 2020)
Introduction: The frequency that idiopathic focal segmental glomerulosclerosis (FSGS) recurs in renal allografts is reportedly 20-50%, but the epidemiology of secondary FSGS in this setting has scarcely been addressed. Objectives: The aim of this study was to examine the incidence, etiology, and subtypes of FSGS in renal allograft recipients and allograft survival in recipients with FSGS. Patients and Methods: As a retrospective review, we examined medical records of 359 consecutive renal allograft recipients (living donors, 329; cadaveric donors, 30). In 121 of these patients, allograft dysfunction or proteinuria prompted biopsies. We compared allograft survival in recipients with and without FSGS. We then determined histologic subtypes of FSGS using the Columbia classification and categorized FSGS as recurrent or de novo, and idiopathic or secondary. Results: Of 121 subjects who were biopsied, six with inadequate specimens (<10 glomeruli) were excluded. Only 17 of those remaining (n=115) were diagnosed as secondary FSGS. Renal allograft survival did not differ significantly in patients with or without FSGS (P=0.953). Subtypes of FSGS were as follows; not otherwise specified (NOS; n=8), collapsing (n=5), cellular (n=2), and perihilar (n=2). Conclusion: Secondary FSGS was observed in 14.5% of biopsies of renal allograft recipients and seemed no significant impact on allograft survival.